Altered T Follicular Helper Cell Subsets and Function in Chronic Lymphocytic Leukemia - Wu, Xun; Fajardo-Despaigne, J. Ernesto; Zhang, Christine; Neppalli, Vishala; Banerji, Versha; Johnston, James B.; Gibson, Spencer B.; Marshall, Aaron J. (Frontiers in Oncology, 2021)
Follicular helper T cells (TFH) have specialized properties in promoting normal B cell activation but their role in chronic lymphocytic leukemia (CLL) is unknown. We find that TFH cells are elevated in CLL patients and are phenotypically abnormal, expressing higher levels of PD-1, TIGIT, CD40L, IFN and IL-21, and exhibiting abnormal composition of TFH1, TFH2 and TFH17 subsets. Frequencies of CD4-positive T cells expressing TFH1 markers and IL-21 were positively correlated with patient lymphocyte counts and RAI stage, suggesting that accumulation of abnormal TFH cells is concomitant with expansion of the leukemic B cell clone. Treatment with ibrutinib led to normalization of TFH frequencies and phenotype. TFH cells identified in CLL bone marrow display elevated expression of several functional markers compared to blood TFH cells. CLL T cell-B cell co-culture experiments revealed a correlation of patient TFH frequencies with functional ability of their CD4-positive T cells to promote CLL proliferation. Conversely, CLL cells can preferentially activate the TFH cell subset in co-culture. Together our results indicate that CLL development is associated with expansion of abnormal TFH populations that produce elevated levels of cytokines and costimulatory molecules which may help support CLL proliferation.